Successful pregnancy in a patient with Ebstein’s anomaly: a case report and review of literature - Sharma, Charu; Singh, Shiv Shankar; Saha, M. K.; Pegu, Bhabani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ebstein’s anomaly, a rare congenital heart disease, has an extremely variable natural history, depending on variety of pathological features. We here describe a case of a patient with Ebstein’s anomaly who had an uneventful vaginal delivery of a healthy term baby. The anomaly was diagnosed during childhood, was not associated with other cardiac anomalies, cyanosis or pre-excitation and the echocardiographic degree of severity was low.